Waqf system and civil society: A reading of the implications and limits of the relationship and the developmental function - Mohamed TAIEB AMOUR; DELLALI Djilali (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
The relationship between religion and politics is one of the most important obstacles to political and economic stability in the Arab world. after adopting the option of nationalism as an ideology and political approach after the first and second Arab revolutions, which was reflected in the level of performance of societal institutions that have always had a leadership in Muslim civilization and the preservation of the societal and institutional structure of the state. Similar to waqf system, which throughout its history formed a balance of the relationship between the state and society, even with the transformations that this system experienced, which led to its development at times, and its decline, shrinkage, and state control over it at other times, especially with the crystallization of the civil society system, whose functions and roles overlapped, to the point of identification in some cases with the Islamic waqf system and its institutions.